Analisis Fatwa Dewan Syariah Wahdah Islamiyah No. D.027/QR/DSR-WI/VII/1435 Tentang Kegiatan Dakwah Muslimah di Malam Hari: Analysis of the Fatwa of the Wahdah Islamiyah Sharia Council No. D.027/QR/DSR-WI/VII/1435 Regarding Muslimah Da'wah Activities at Night - Muttazimah, Muttazimah; Iskandar, Iskandar; Riska Amalia Putri (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2024)
Da'wah is a duty for every Muslim, including women, as a reflection of gender equality in Islam. However, Muslim women must adhere to the principles of Sharia. Fatwa DSR-WI No. D.027/QR/DSR-WI/VII/1435 establishes guidelines and limitations to be observed when engaging in da'wah, especially at night, to uphold the dignity, modesty, and welfare of Muslim women in both this world and the Hereafter. This study analyzes the fatwa and methods of ijtihad related to nighttime da'wah activities for Muslim women. The issues examined include the analysis of the fatwa and the ijtihad methodology of the Wahdah Islamiyah Sharia Council regarding women’s da'wah at night. Using a descriptive qualitative approach based on literature studies and normative and social methods, this study found that the Sharia Council’s fatwa on women’s nighttime da'wah is grounded in public welfare, referencing the Qur'an, hadith, fiqh principles, and maqāṣid al-sharī'ah, emphasizing the importance of safety, morality, and the prevention of harm. The Sharia Council applies a systematic ijtihad methodology to ensure relevance and practical application in daily religious life. This study contributes to a deeper understanding of ijtihad methodology, fiqh principles, and maqāṣid al-sharī'ah, while providing practical guidance for female da'wah activists in developing policies and effective da'wah programs.